Factors influencing assessment in higher education: Empirical evidence from physical education and fitness compulsory courses in Indonesia - Kristiyandaru, Advendi; Prakoso, Bayu Budi; Fithroni, Hijrin; Primanata, Dani; Hartati, Sasminta Christina Yuli; Kartiko, Dwi Cahyo (LPMPP Universitas Negeri Yogyakarta, 2023)
The present study delves into the multifarious factors that underpin students' learning assessment in higher education. Through the utilisation of an exploratory sequential mixed methods design, the researchers scrutinise the evaluation of 5,564 students by 23 lecturers, taking into consideration 9 characteristics. To that end, ANOVA and T-test are employed to analyse the mandatory course, and three lecturers who embody distinct criteria are interviewed, and their responses are subjected to a thematic analysis. The results indicate that assessment results are significantly different based on lecturers' working experience (teaching experience [F= 20.1, p= 0.000] and age [F= 48.6, p= 0.000]), academic background (department [F= 33.8, p= 0.000] and skills [F= 30.17, p= 0.000]), and teaching load (credit unit (credit unit) [F= 48.7, p= 0.000], number of classes taught [F= 61.4, p= 0.000] and teaching partners [F= 79.3, p=0.000]). Meanwhile, there is no difference in assessment results based on lecturers' qualifications (certificates [t= -0.587, p= 0.557] and latest degree [F= 2.56, p= 0.074]). The qualitative data reveals that four crucial factors - idealism, mindset, grading standard, and perspective - account for the variance observed in compulsory courses. The study's results underscore the need for universities to devise pedagogical strategies based on lecturers' attributes, as these factors bear a direct impact on the attainment of the desired graduate profiles as reflected in students' academic performance in specific courses.